O efeito suspensivo aos embargos à execução fiscal após o advento da Lei 11.382/2006 - Ferreira, Olívia Tonello Mendes (2009)
The present work has the objective of analyzing if the stays of tax foreclosure should always be received with suspensive effect or if, after the advent of Law 11.382/2006, which had altered significantly the Code of Civil Procedure, mainly concerning the discipline of civil execution by means of extrajudicial title, the concession of the suspensive effect is conditioned to the presence of fumus boni iuris, periculum in mora and judgment security, in the terms of the new art. 739-A and its first paragraph. Since this is a study with scientific aims, we will first discourse about the issues related to Law Philosophy and the General Theory of Law, in which the adopted reference system will be identified, as well as establishing the premises to be adopted along the study, going through the notion of juridical system, characterization of antinomies and the ways of solving those conflicts. Afterwards, some requirements to the achievement of the execution and of some of the applying principles to the process mentioned will be approached. Next, the systematic of embargos to the civil execution of extrajudicial executive title will be analyzed, tracing a comparative analysis of the main changes made by the advent of law 11.382/2006. Then, some notes about the objective responsibility of the State will be made so that the specificities of the executive juridical-tributary relation formed between the State and the Private in the process of tax execution can be analyzed. Once these specificities are analyzed, we will discourse about the norms to be applied